Effect of Nerve-Cutting Technique on Nerve Microstructure and Neuroma Formation - Rummings, Wayne A.; Honeycutt, P. Barrett; Jernigan, Edward W.; Weinhold, Paul S.; Draeger, Reid W. (Journal of Hand and Microsurgery, 2019)
Background Peripheral neuroma formation results from partial or complete nerve division. Elucidating measures to prevent the development of peripheral neuromas is of clinical importance. The aim of this study was to determine the effect of various surgical nerve-cutting techniques on nerve microstructure and resultant neuroma formation.Methods Twenty Sprague-Dawley rats were randomly assigned to one of the following nerve-cutting techniques: No. 15 scalpel blade with tongue depressor, micro-serrated scissors, nerve-cutting guide forceps with straight razor, and bipolar cauterization. The right sciatic nerve was transected using the assigned nerve-cutting technique. Neuromas were harvested 6 weeks postoperatively, and samples were obtained for histologic analysis. The contralateral sciatic nerve was transected at euthanasia and analyzed with histology and with scanning electron microscopy in a subset of the rats.Results Fifteen of the 20 rats survived the 6-week experiment. Scanning electron microscopy of the No. 15 scalpel blade group showed the most visual damage and disorganization whereas the nerve-cutting guide forceps and micro-serrated scissors groups resulted in a smooth transected surface. Bipolar cauterization appeared to enclose the fascicular architecture within a sealed epineurium. Each neuroma was significantly larger than contralateral controls. There were no significant differences in neuroma caliber between nerve transection groups. No substantial differences in microstructure were evident between transection groups.Conclusion Despite disparate microscopic appearances of the cut surfaces of nerves using various nerve-cutting techniques, we found no significant differences in the caliber or incidence of neuroma formation based on nerve-cutting technique. Nerve-cutting technique used when transecting peripheral nerves may have little bearing on the formation or size of resultant neuroma formation.
Keywords: neuroma; nerve microstructure; nerve cutting; nerve surgery; peripheral neuroma